ANALISIS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE PADA PEMBELAJARAN IPAS SEKOLAH DASAR: KAJIAN LITERASI - Zyra Aurelia Putri, Putu; Ari Winangun, I Made; Lisna Handayani, Ni Nyoman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This literature review discusses the application of the Think Talk Write cooperative learning model in science learning in elementary schools. Science learning in elementary schools still faces obstacles such as low student activity, lack of variety in learning methods, and suboptimal conceptual understanding, which impacts student learning outcomes. This study aims to analyze the application of the Think Talk Write cooperative learning model as an alternative to improve the quality of science learning. The method used is a literature review with a Systematic Literature Review (SLR) approach using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow. A total of eleven scientific articles were found in the identification stage, then selected through a screening and feasibility stage based on topic relevance, variable suitability, and completeness of content until five articles were obtained that met the criteria for further analysis. The research stages include identification, article selection, content analysis, and systematic synthesis of research results. The results of the study indicate that the Think Talk Write model has a positive impact on science learning, as demonstrated by improved learning outcomes, active student participation, and conceptual understanding through structured thinking, discussion, and writing activities. Thus, this model is considered effective and relevant to implement to create active, meaningful, and student-centered learning.